(untitled) (Revista Apotheke, 2021)
We herein bring a descriptive approach to Pierre Verger’s photographic art focused on his view of Afro-Brazilian culture in Bahia. We discuss here Verger’s ethnographic looked forward at the Afro-Brazilian population, which brings a language of intersection between photography and ethnology.The images that reflect the cutout of religious syncretism in Candomblé rituals are understood as an own visual language, not limited to a simple documentary. Images are understood as one of the forms of manifestation of Afro-Brazilian art which represents a strategy of resistance by African slaves in Bahia, through its cultural elements coming from a servile regime, with values ​​that emerged in the new environment. It is intended, therefore, to contribute to the knowledge of the interface between cultural identity / Afro-descendant ancestry and the art of Verger’s photographs, in the perspective of the process of strengthening the cultural identity of the Afro-descendant community in Bahia.